Pengaruh Model Pembelajaran Kontekstual Berbasis Kearifan Lokal terhadap Pemahaman Materi Bangun Ruang di Sekolah Dasar - Fitri Mardayanti; Aribah Capah; Khofifah Indah T; Septi Qorima Sitorus (International Forum of Researchers and Lecturers, 2025)
Students' understanding of the concept of nets and surface area of spatial shapes is still relatively low due to the abstract nature of the material and the lack of connection with real life. This study aims to determine the effect of contextual learning models based on North Sumatra local wisdom on improving elementary school students' concept understanding. The method used is Systematic Literature Review (SLR) by analyzing various relevant sources from 2019 to 2024. The results showed that the integration of local cultural elements, such as Batak traditional houses (Rumah Bolon), gorga carvings, and traditional crafts, can help students understand mathematical concepts more concretely. This approach encourages better spatial visualization and calculation skills, and increases students' motivation and active participation. Learning becomes more meaningful as students can relate the material to their cultural environment. However, challenges such as limited learning resources and teacher readiness are still barriers to implementation. Therefore, training for teachers and development of local culture-based teaching materials are needed. This research contributes to the development of contextual learning strategies that are more relevant to students' cultural background, especially in mathematics education at the primary school level.